Mammea B/BA Isolated From the Seeds of Mammea americana L. (Calophyllaceae) is a Potent Inhibitor of Methicillin-Resistant Staphylococcus aureus - Yina Pájaro-González; Yina Pájaro-González; Andrés F. Oliveros-Díaz; Julián Cabrera-Barraza; Eduardo Fernández-Daza; Niradiz Reyes; Oscar A. Montes-Guevara; Daneiva Caro-Fuentes; Luis Franco-Ospina; Wiston Quiñones- Fletcher; Cassandra L. Quave; Fredyc Díaz-Castillo (Frontiers Media S.A., 2022)
Staphylococcus aureus remains a pathogen of high concern in public health programs worldwide due to antibiotic resistance and emergence of highly virulent strains. Many phytochemicals have demonstrated activity against S. aureus and other Gram-positive bacteria, but the minimum inhibitory concentration (MIC) values comparable to commonly used antibiotics are needed. In the present study, bio-guided fractionation of the ethanol extract of seeds of Mammea americana L. (Calophyllaceae) throughout the antibacterial activity, against S. aureus strains that are sensitive and resistant to methicillin, led to the isolation of four coumarins identified as mammea B/BA, mammea B/BC, mammea A/AA cyclo D and mammea A/AA cyclo F, and a mixture of mammea B/BA cyclo F plus mammea B/BD cyclo F. The extract inhibited the growth of S. aureus with MIC values of 2-4 μg/ml and Mammea B/BA (MaBBA) presented MIC values in a range between 0.5 and 1.0 μg/ml in six methicillin-sensitive strains and eight methicillin-resistant strains evaluated. We consider MaBBA the most potent of all mammea coumarins reported to date, according to the literature review carried out at the time of writing of this article. Toxicity assessment in vivo against the nematode Caenorhabditis elegans and in vitro against human fibroblasts of the extract and the compound MaBBA indicated that both had low toxicity.